Intergenerational transmission of family meal patterns from adolescence to parenthood: longitudinal associations with parents’ dietary intake, weight-related behaviours and psychosocial well-being - Berge, Jerica M (Public Health Nutr, 2017)
OBJECTIVE: The present study examined longitudinal associations between four family meal patterns (i.e. never had regular family meals, started having regular family meals, stopped having regular family meals, maintained having regular family meals) and young adult parents’ dietary intake, weight-related behaviours and psychosocial well-being. In addition, family meal patterns of parents were compared with those of non-parents. DESIGN: Analysis of data from the longitudinal Project EAT (Eating and Activity in Adolescents and Young Adults) study. Linear and logistic regressions were used to examine the associations between family meal patterns and parents’ dietary intake, weight-related behaviours and psychosocial well-being. SETTING: School and in-home settings. SUBJECTS: At baseline (1998; EAT-I), adolescents (n 4746) from socio-economically and racially/ethnically diverse households completed a survey and anthropometric measurements at school. At follow-up (2015; EAT-IV), participants who were parents (n 726) and who were non-parents with significant others (n 618) completed an online survey. RESULTS: Young adult parents who reported having regular family meals as an adolescent and as a parent (‘maintainers’), or who started having regular family meals with their own families (‘starters’), reported more healthful dietary, weight-related and psychosocial outcomes compared with young adults who never reported having regular family meals (‘nevers’; P<0·05). In addition, parents were more likely to be family meal starters than non-parents. CONCLUSIONS: Results suggest that mental and physical health benefits of having regular family meals may be realized as a parent whether the routine of regular family meals is carried forward from adolescence into parenthood, or if the routine is started in parenthood.